2019
DOI: 10.1097/rct.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cone-Beam Computed Tomography and Multislice Computed Tomography in the Assessment of Extremity Fractures

Abstract: Objectives The aims of this study were to evaluate the agreement between cone-beam computed tomography (CBCT) and multislice computed tomography for the characterization of extremity fractures and to compare image quality, radiation dose, and patient tolerance. Methods Thirty-six patients with suspected fracture affecting distal extremities or who required preoperative fracture assessment were enrolled prospectively. Each patient underwent CBCT and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Historically, this decision-making process has been dominated by concern for the negative sequelae of a non-union fracture [36,37] and, when initial radiographs are equivocal or in case of complex fractures (articular involvement or fragments angulation-dislocation), further multiplanar, high-resolution imaging with CT can be needed [16,17,20,21]. The choice between CBCT and MSCT may be justified by costs and performance characteristics: CBCT is a more cost-effective diagnostic modality due to high sensitivity and lower costs compared with MSCT [17][18][19]22]. The sensitivity and specificity of MSCT and CBCT are both very high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, this decision-making process has been dominated by concern for the negative sequelae of a non-union fracture [36,37] and, when initial radiographs are equivocal or in case of complex fractures (articular involvement or fragments angulation-dislocation), further multiplanar, high-resolution imaging with CT can be needed [16,17,20,21]. The choice between CBCT and MSCT may be justified by costs and performance characteristics: CBCT is a more cost-effective diagnostic modality due to high sensitivity and lower costs compared with MSCT [17][18][19]22]. The sensitivity and specificity of MSCT and CBCT are both very high.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of finger fracture and performance characteristics of imaging studies were derived from published information [1,2,18,19]. Performance characteristics and utility values of cross-sectional imaging were derived from published information: MSCT sensitivity in the diagnosis of finger fractures is 94% and specificity is 92% [18][19][20][21]. Sensitivity and specificity for CBCT amount to 91% and 93%, respectively [18,19,22,[25][26][27].…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study by Dubreuil et al. compared image quality and radiation dose between cone-beam CT and multislice CT [ 47 ]. They found that cone-beam CT delivered significantly less radiation to the patient (average CTDI 2.8 mGy vs 13.1 mGy) than multislice CT while providing high-enough-quality images for fracture classification [ 47 ].…”
Section: The As Low As Reasonably Achievable Principlementioning
confidence: 99%